2017
DOI: 10.1055/s-0037-1615290
|View full text |Cite
|
Sign up to set email alerts
|

New Targets for the Prevention of Chronic Rejection after Thoracic Organ Transplantation

Abstract: The gold standard for the treatment of terminal heart failure and irreversible lung diseases includes thoracic organ transplantation. The major obstacle for long-term survival after successful transplantation is chronic rejection, an ongoing immunomodulatory disease so far without effective therapy. Therefore, the aim of this review is to elucidate scientific efforts targeting different new mechanisms of cardiac allograft vasculopathy (CAV) and chronic lung allograft dysfunction (CLAD). For this purpose, we pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…10,11 In summary, our findings affirm both in vitro-and in vivo-activated hPlts as an isolated factor responsible for the development of transplant arteriosclerosis in a humanized mouse artery xenograft model and support the therapeutic usage of the antiplatelet agents such as clopidogrel for effectively reducing transplant arteriosclerosis in experimental vascular grafts. 10,11 This humanized C57/Bl6-Rag2 −/− γc −/− mouse xenograft model may be useful to investigate further cell subpopulations required for the development of transplant arteriosclerosis and to test novel therapeutic strategies 46,47 as well as drug interactions altering the platelet response and ultimately to prevent the development of CAV in human patients.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In summary, our findings affirm both in vitro-and in vivo-activated hPlts as an isolated factor responsible for the development of transplant arteriosclerosis in a humanized mouse artery xenograft model and support the therapeutic usage of the antiplatelet agents such as clopidogrel for effectively reducing transplant arteriosclerosis in experimental vascular grafts. 10,11 This humanized C57/Bl6-Rag2 −/− γc −/− mouse xenograft model may be useful to investigate further cell subpopulations required for the development of transplant arteriosclerosis and to test novel therapeutic strategies 46,47 as well as drug interactions altering the platelet response and ultimately to prevent the development of CAV in human patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac allograft vasculopathy still is the most important long term complication after heart transplantation and many efforts are taken to find a way to prevent its development. 33 In the current study, we tested nintedanib, a tyrosine kinase inhibitor with antagonistic effects on different growth factor receptors, for its impact on CAV. Results of our study revealed that treatment with nintedanib (1) significantly reduced CAV development after allogeneic aortic transplantation in mice, (2) which was characterized by significantly reduced amounts of neointimal smooth muscle cells accompanied by a decreased immigration of DCs and T cells into the neointima, and (3) by reduced expression of PDGF receptors α and β as well as their ligand PDGF-B.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 7 , 34 Nintedanib significantly inhibited this process in our mouse model which can be explained by the effects of the targeted tyrosine kinase receptors (TKRs). PDGFRα + β strongly mediate SMC proliferation and migration after ligand binding, 11 , 30 , 31 while VEGFR1 + 2 only mediate cell migration, 32 , 33 but additionally seem to be able to potentiate the mitogenic effect of FGF. 32 FGF again is a very potent factor for SMC proliferation 34 via its receptors FGFR1 and FGFR2.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelium plays a key role in the onset and progression of CAV [ 1 ]. Endothelial dysfunction is a typical feature of many cardiovascular diseases (CVDs) [ 8 ], and it is also an early feature of CAV, and it was found to progress with increasing time post-HTx [ 9 , 10 ]. Typically, coronary angiography is used to monitor the progress of CAV [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both immunologic and nonimmunologic (CVD) risk factors contribute to the development of CAV [ 22 , 23 , 24 ]. Intriguingly, there appears to be a complex interplay between both factors, ultimately leading to endothelial injury and an exaggerated repair response [ 2 , 9 , 10 ]. Traditional risk factors for the development of both CVD and CAV include dyslipidemia, diabetes, and hypertension [ 25 ].…”
Section: Introductionmentioning
confidence: 99%